2007
DOI: 10.14227/dt140407p15
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of In Vitro Release Methods for the Evaluation of Oxytocin Release from Pluronic® F127 Parenteral Formulations

Abstract: The objective of these studies was to develop a discriminatory in vitro release test for assessing formulation factors that may affect oxytocin (OT) release during formulation development studies of a Pluronic® F127 OT in situ gel-forming parenteral dosage form. An appropriate release assessment method should be able to discriminate between the performance of different formulation compositions (1, 2), and this was the primary criterion used for selection of an appropriate test procedure during the test method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Once again, the value for f 2 indicates that there is similarity between the two profiles, whereas the value for f 1 suggests that the profiles are different. While the use of only f 2 is considered in decision making with respect to the similarity of dissolution curves, it has been suggested that both f 1 and f 2 values should be used during formulation development studies to facilitate better decision making (24). In addition, the testing of an additional six units may also be useful to ensure that a true difference exists.…”
Section: Impact Of Mesh Screen Pore Sizementioning
confidence: 99%
“…Once again, the value for f 2 indicates that there is similarity between the two profiles, whereas the value for f 1 suggests that the profiles are different. While the use of only f 2 is considered in decision making with respect to the similarity of dissolution curves, it has been suggested that both f 1 and f 2 values should be used during formulation development studies to facilitate better decision making (24). In addition, the testing of an additional six units may also be useful to ensure that a true difference exists.…”
Section: Impact Of Mesh Screen Pore Sizementioning
confidence: 99%
“…PF-127 thermosensitive gel has shown to prolong the release of various proteins and also extended stability [154,155]. In a recent work, Akash et al have evaluated sustained delivery of IL-1 receptor antagonist (IL-1Ra) from PF127 based thermosensitive gel both in vitro and in vivo [156158].…”
Section: Colloidal Delivery Systemsmentioning
confidence: 99%
“…From various previous studies, it has been proved that PF127 is safe for the sustained delivery of various proteins such as IL-2 [31], insulin [29], [32], recombinant hirudin [33], oxytocin [34] and lysozyme [35], and prolongs the stability of proteins [26][29]. From clinical perspective, our investigations that are derived from an experimental protocol could stimulate further clinical trials on type 2 diabetic patients to expedite therapeutic uses of PF127 for safe and effective delivery of IL-1Ra that exhibit its sustained release effects devoid of altering normal physiological functions of body and protecting the efficacy of encapsulated IL-1Ra till its delivery to the target site.…”
Section: Discussionmentioning
confidence: 99%